Miss Dulce extranjera o ang paghahanap kay Miss B (dulang may dalawang yugto) - Tiatco, Sir Anril Pineda (University of the Philippines Press, 2011)
A play based on historical documents. The two writers joining a competition, with Dr. Jose Rizal and Josephine Bracken as their main subjects and how they argue on the various significant events in their lives.